2021
DOI: 10.1097/wnr.0000000000001630
|View full text |Cite
|
Sign up to set email alerts
|

Functional plasticity in lateral hypothalamus and its prediction of cognitive impairment in patients with diffuse axonal injury: evidence from a resting-state functional connectivity study

Abstract: Objective Diffuse axonal injury (DAI) is a common pathological process after traumatic brain injury, which may cause survivors severe functional disorders, including cognitive impairment and physical disability. Recent literature indicated lateral hypothalamus and medial hypothalamus damage during DAI. Thus, we aim to investigate whether there is imaging evidence of hypothalamic injury in patients with DAI and its clinical association.Methods Twenty-four patients with diagnosed DAI and 26 age and sex-matched h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…26 Patients with diffuse axonal injury showed reduction in hypothalamic--basal ganglia and cingulate gyrus rsFC in association with cognitive impairment. 27 In rodents the formation of object recognition memory was regulated via hypothalamic circuits. 28 These findings implicate the hypothalamus in learning and memory through mechanisms beyond those involved in energy homeostasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Patients with diffuse axonal injury showed reduction in hypothalamic--basal ganglia and cingulate gyrus rsFC in association with cognitive impairment. 27 In rodents the formation of object recognition memory was regulated via hypothalamic circuits. 28 These findings implicate the hypothalamus in learning and memory through mechanisms beyond those involved in energy homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy individuals, physiological responses to trauma and stress were associated with hypothalamic activity and functional connectivity 26 . Patients with diffuse axonal injury showed reduction in hypothalamic––basal ganglia and cingulate gyrus rsFC in association with cognitive impairment 27 . In rodents the formation of object recognition memory was regulated via hypothalamic circuits 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Severe cognitive impairment and physical disability were caused by lateral hypothalamus and medial hypothalamus damage during DAI ( Wang et al, 2021 ). HVLT, TMT, and Rey–Osterrieth Complex Figure test were performed by Macruz et al (2022) to reveal the impairment and recovery of episodic verbal memory, attention, and executive function of DAI patients.…”
Section: Discussionmentioning
confidence: 99%
“…After an investigation into reader concerns, the Editorial Office found that passages had been directly plagiarized and/or slightly modified from “Functional plasticity in lateral hypothalamus and its prediction of cognitive impairment in patients with diffuse axonal injury: evidence from a resting-state functional connectivity study”. [ 2 ]…”
mentioning
confidence: 99%